Peningkatan Kreativitas Melukis melalui Media Cotton Bud pada Anak Kelompok B Tk Pertiwi Karangasem - Aminah, Siti (Didaktika, 2022)
Developing children's creativity, especially painting creativity, children can express their imagination and can also learn to control their hands, coordinate their thoughts, eyes, and hands, and express themselves through art. Children can be as creative as they wish in arranging colors when painting. Based on this background, this research problem can be formulated, namely: "how to increase painting creativity through Cotton Bud media in group B children at TK Pertiwi Karangasem, Tanon District, Sragen Regency?" The research subjects of this class action were carried out in group B with a total of 15 children and an age range between 5.5 to 6 years. With a total of 7 male students and 8 female students. Data collection techniques used in this study are observation and documentation. Based on data from a study on group B children at TK Pertiwi Karangasem, Tanon District, Sragen Regency. Recapitulation of pre-action children's painting creativity, cycle I and cycle II above the average percentage in the pre-cycle of 42.00% with the Starting Development (MB) criteria, in cycle I increased by 70.22% with the Expected Developing criteria (BSH), and in cycle II it experienced an increase of 87.67% with the criteria of Very Good Development (BSB). After seeing the results of the data on children's painting creativity ability above, it can be seen that painting activities using Cotton Buds provide opportunities for children to express their creativity, and put forward ideas in making works that are original according to the wishes of the child. The process of learning activities through painting activities with Cotton Bud media is more interesting and fun for children. The materials used encourage children to express themselves in the form of works made by children.